Design of Unidirectional Vehicular Traffic With a Two-Dimensional Topological Structure - Hiroya Tanaka; Keita Funayama (IEEE Open Journal of Intelligent Transportation Systems)
Vehicular transportation design and control are critical topics of research. In two-dimensional topological systems, edge states exist at the boundary and support transport along the system edges. In this study, we demonstrate the directional flow of vehicular traffic in a hexagonal street network with a two-dimensional topological structure. We model the network structure by the topology of vertices and edges, and vehicular transport as a symmetric random walk between the vertices. We show that the proposed structure provides a macroscopically unidirectional traffic flow to a group of vehicles. Furthermore, we note that such unidirectional properties deteriorate because of the decay of the topological edge mode. To overcome the disappearance of traffic unidirectionarity, we propose a strategy for controlling the entry–exit timing of vehicles in a street network and confirm its effectiveness through simulations. The proposed vehicle management strategy sustainably allows unidirectional traffic in street networks. Our work thus provides a critical building block for designing and controlling transportation networks.